GAINING COMPETITIVE ADVANTAGE IN THE GAS BOILERS MARKET OF VOJVODINA THROUGH INTEGRATED MARKETING COMMUNICATIONS - Jovičić, Dragoljub; Vranješ, Marija; Stankov, Biljana (International Journal of Economic Practice and Policy, 2015)
Since the appearance of marketing and implementation of marketing concept in practice, the importance of the marketing mix, through which organizations adapt their offer to targeted customer segments, was emphasized . Regardless of the fact that the product is commonly referred to as the basic (key) instrument of the marketing mix, in the last ten years, due to the rapid and strong development of science, technology, especially information technology, business and society in general, integrated marketing communications (IMK) are becoming increasingly important, without which organizations can not even begin, or end, any significant marketing activity. In this context, the aim of the authors of this study was to investigate the importance of integrated marketing communications on the placement of gas boilers, i.e. on the market share of individual producers in the market of Vojvodina, which also represents the basic hypothesis of the research. Research results confirmed the basic hypothesis as well as an extraordinary influence of IMK to the market share of producers in the placement of gas boilers. Supplementary hypothesis was not confirmed, advertising is not a key promotional instrument. Thanks to  the specific characteristics, primarily the high technical complexity of gas boilers, a key promotional instrument are education and training of sales and installation staff in the marketing channels, which operate on the market of Vojvodina.
Keywords: integrated marketing communication; marketing mix; holistic marketing; COMPETITIVE ADVANTAGE; market of gas boilers